KAJIAN METODE DISCOVERY LEARNING DAN RESITASI DALAM MENINGKATKAN MINAT BELAJAR IPA SISWA SD - rima lutfi; Nurwulan Purnasari (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2020)
This research aims to review the application of discovery learning methods and recitation methods towards student's learning interest in primary school. This research uses meta-analysis model and the data was collected from theories and research result in e-journal from Google Cendekia and IAIN's library. Data analysis performed with a qualitative descriptive step. This study revealed that discovery learning methods was able to increase student's learning interest between 11% until 49% with average point 21,39%. Based on the results of the analysis, it concluded that the application of discovery learning methods and recitation learning methods in learning could increase primary student learning interest, especially in science subjects.